IMPACTO DA INTRODUÇÃO DA ALBUFEIRA DE ALQUEVA NO MODELO DE PREVISÃO AROME - Assunção, Sónia (2018)
Although the floodgates of the Alqueva dam were closed in 2002, giving rise to the largest artificial lake in Western Europe, its possible effects on the weather in Portugal are not being taken into account by the operational models of weather forecasting used in IPMA. Thus, it is necessary to introduce the physiography of the lake in the model under study (AROME), and to validate it by analysing statistically as well as meteorologically the differences between the model simulations with and without Alqueva and to compare these results with observations.